SOME REMARKS ON AN ALTERNATIVE APPROACH FOR BOLTZMANN DISTRIBUTION OF HYDROGEN ATOMS - Fabiano, Nicola; Radenović, Stojan (Bulletin of Natural Sciences Research, 2020)
We propose an alternative approach to Boltzmann distribution concerning the hydrogen atom and compare our results to previous formalism for some observables.
Keywords: Hydrogen atom; Partition function; Tsallis model